Energy barriers and mechanisms in solid–solid polymorphic transitions exhibiting cooperative motion. Issue 23 (21st April 2016) - van den Ende, Joost A.; Ensing, Bernd; Cuppen, Herma M.
Abstract : The cooperative behaviour at the molecular scale of the β → α polymorphic transition ofdl -norleucine is studied with different computational approaches. Abstract : Understanding solid–solid polymorphic transitions within molecular crystals on the molecular scale is a challenging task. It is, however, crucial for the understanding of transitions that are thought to occur through cooperative motion, which offer an interesting perspective for future applications. In this paper, we study the energy barriers and mechanisms involved in the β → αdl -norleucine transition at the molecular scale by applying different computational techniques. We conclude that the mechanism of the transition is a cooperative movement of bilayers through an intermediate state. The results indicate that local fluctuations in the conformations of the aliphatic chains play a crucial role in keeping the cooperative mechanism sustainable at large length scales. We have characterized the intermediate state.